PPS / PPE composite material and preparation method and application thereof

By using graft copolymers of specific main chains and side chains in PPS/PPE composites, the problems of incompatibility and viscosity differences in materials are solved, and the effects of high elongation of break and low carbonization points are achieved, which improves the overall performance of the material.

CN119708844APending Publication Date: 2025-03-28KINGFA SCI & TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411963100.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-30
Publication Date
2025-03-28

AI Technical Summary

Technical Problem

Due to incompatibility and viscosity differences, PPS/PPE composites have low elongation of break and many carbonization points, and the use of conventional compatibility agents will reduce heat resistance.

Method used

Graft copolymers of specific main chain and side chains are used as components of PPS/PPE composites to improve compatibility between the two and improve elongation of break while maintaining heat resistance.

Benefits of technology

The compatibility and elongation of break of PPS/PPE composite materials are significantly improved, the generation of carbonization points is reduced, and the overall quality of the material is improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005217663700000061
    Figure BDA0005217663700000061
  • Figure BDA0005217663700000071
    Figure BDA0005217663700000071
  • Figure BDA0005217663700000072
    Figure BDA0005217663700000072
Patent Text Reader

Abstract

The invention discloses a PPS / PPE composite material as well as a preparation method and application thereof, and relates to the technical field of engineering plastics. The invention provides a PPS / PPE composite material. The PPS / PPE composite material comprises the following components in parts by weight: 50-90 parts of polyphenylene sulfide resin, 5-20 parts of polyphenyl ether resin and 3-10 parts of a graft copolymer, wherein the grafted copolymer comprises a main chain and a side chain, the main chain is one of polyethylene, polypropylene, an ethylene copolymer and a propylene copolymer, and the side chain is one of polystyrene and a styrene copolymer; the pH value of the polyphenylene sulfide resin is 5 to 8. According to the invention, the PPS / PPE composite material with good heat resistance, high elongation at break and few carbonization points is prepared by using the graft copolymer of the specific main chain and side chain.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of engineering plastics, in particular to a PPS / PPE composite material and a preparation method and application thereof. Background Art

[0002] Polyphenylene sulfide (PPS) resin has the advantages of high temperature resistance, corrosion resistance, radiation resistance, flame retardancy, non-toxicity, excellent mechanical and electrical properties, and good dimensional stability of products. It can be used for high temperature resistant pipes. Polyphenylene ether (PPE) resin has good mechanical properties, electrical properties, heat resistance, flame retardancy and chemical stability. Polyphenylene sulfide / polyphenylene ether (PPS / PPE) alloy has the advantages of PPS and PPE, such as high temperature resistance, flame retardancy, chemical corrosion resistance, etc., while overcoming the shortcomings of PPS brittleness, low melt viscosity, injection molding flash overflow and difficulty in molding, and PPE's inability to resist solvents and excessive melt viscosity. However, PPS and PPE are incompatible polymers, and the viscosity difference between the two is large. There is no interaction force between the molecular segments during mixing, and they cannot be mixed evenly, making the elongation at break of the material very low, and it cannot be continuously extruded and molded after mixing. The compatibility problem can be improved by adding some conventional compatibilizers, but due to its insufficient compatibility effect, the heat resistance of the material will be reduced; or due to its own insufficient heat resistance, it will decompose and produce carbides during processing, forming carbonization points, resulting in poor quality of the extruded product.

[0003] Therefore, a PPS / PPE composite material with good heat resistance, high elongation at break and few carbonization points has broad application prospects. Summary of the invention

[0004] Based on this, the purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a PPS / PPE composite material with good heat resistance, high elongation at break and few carbonization points, as well as a preparation method and application thereof.

[0005] To achieve the above-mentioned purpose, the technical scheme adopted by the present invention is: a PPS / PPE composite material, comprising the following components in parts by weight: 50-90 parts of polyphenylene sulfide resin (PPS), 5-20 parts of polyphenylene ether resin (PPE), and 3-10 parts of graft copolymer; wherein the graft copolymer comprises a main chain and a side chain, the main chain is one of polyethylene (PE), polypropylene (PP), ethylene copolymer, and propylene copolymer, and the side chain is one of polystyrene (PS) and styrene copolymer; the pH value of the polyphenylene sulfide resin is 5-8.

[0006] Preferably, the main chain of the graft copolymer is one of an ethylene copolymer and a propylene copolymer.

[0007] Preferably, the ethylene copolymer includes one of ethylene-glycidyl methacrylate (EGMA), ethylene-ethyl acrylate copolymer (EEA), and ethylene-butyl acrylate copolymer (EBA); the propylene copolymer includes one of propylene-glycidyl methacrylate (PGMA) and propylene-ethyl acrylate copolymer (PEA).

[0008] Preferably, the styrene copolymer includes one of styrene-acrylonitrile copolymer (AS) and styrene-acrylonitrile-glycidyl methacrylate copolymer (P(GMA / AS)).

[0009] Preferably, the graft copolymer is one of a graft copolymer of main chain PE and side chain PS, a graft copolymer of main chain PE and side chain AS, a graft copolymer of main chain EBA and side chain PS, a graft copolymer of main chain PP and side chain AS, a graft copolymer of main chain EGMA and side chain PS, and a graft copolymer of main chain EEA and side chain AS.

[0010] Preferably, in the graft copolymer, the main chain accounts for 40-80% by mass of the graft copolymer, and the side chain accounts for 20-60% by mass of the graft copolymer; when the side chain is a styrene copolymer, acrylonitrile accounts for 30-80% by mass of the styrene copolymer, and styrene accounts for 20-70% by mass of the styrene copolymer.

[0011] Preferably, the pH value of the polyphenylene sulfide resin is tested by dissolving 50 g of PPS resin in 500 mL of aqueous solution and stirring evenly, standing for 30 minutes and testing with a pH meter to obtain the pH value of the PPS resin.

[0012] Preferably, the weight percentage of the PPS resin in the PPS composite material is not less than 60%.

[0013] The present invention selects a graft copolymer with a specific main chain and side chain, which can take into account both the PPS and PPE components, can effectively improve the compatibility of PPS / PPE, and can also improve the elongation at break of the material while maintaining heat resistance. At the same time, the use of the graft copolymer with a specific main chain and side chain of the present invention can produce very little carbide during decomposition during processing, and the quality of the PPS / PPE alloy is better.

[0014] Optionally, the weight parts of the PPS resin are 50 parts, 51 parts, 53 parts, 55 parts, 58 parts, 60 parts, 61 parts, 63 parts, 65 parts, 68 parts, 70 parts, 72 parts, 75 parts, 80 parts, 82 parts, 85 parts, 88 parts, 90 parts or any two of the range values; the weight parts of the PPE resin are 5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts , 9.5 parts, 10 parts, 11 parts, 12 parts, 13 parts, 14 parts, 15 parts, 16 parts, 17 parts, 18 parts, 19 parts, 20 parts or any two of the range values; the weight parts of the graft copolymer are 3 parts, 3.5 parts, 4 parts, 4.5 parts, 5 parts, 6 parts, 6.5 parts, 7 parts, 7.5 parts, 8 parts, 8.5 parts, 9 parts, 9.5 parts, 10 parts or any two of the range values.

[0015] The inventors found in actual experiments that when the main chain is one of ethylene copolymers and propylene copolymers, the specific flexible main chain can be well entangled with PPS resin and PPE resin, thereby significantly improving the compatibility effect even at a very low addition amount, which can better improve heat resistance and elongation at break and reduce carbonization point.

[0016] Preferably, the PPS / PPE composite material comprises the following components in parts by weight: 70-80 parts of polyphenylene sulfide resin, 10-15 parts of polyphenylene ether resin, and 5-8 parts of graft copolymer.

[0017] Preferably, the polyphenylene sulfide resin has a melt mass flow rate of ≤300 g / 10 min at a test temperature of 316° C. and a load of 5 kg according to ISO 1133-2022; the polyphenylene ether resin has a melt mass flow rate of 10-40 g / 10 min at a test temperature of 315° C. and a load of 10 kg according to ISO 1133-2022; and the graft copolymer has a melt mass flow rate of <2 g / 10 min at a test temperature of 190° C. and a load of 2.16 kg according to ISO 1133-2022.

[0018] Optionally, the polyphenylene sulfide resin has a melt mass flow rate of one or two range values ​​of 300 g / 10 min, 280 g / 10 min, 250 g / 10 min, 200 g / 10 min, 150 g / 10 min, 130 g / 10 min, 100 g / 10 min, 80 g / 10 min, 70 g / 10 min, 60 g / 10 min, 50 g / 10 min under the conditions of a test temperature of 316° C. and a load of 5 kg according to ISO 1133-2022.

[0019] Optionally, the polyphenylene ether resin has a melt mass flow rate in the range of one or any two of 10 g / 10 min, 15 g / 10 min, 20 g / 10 min, 25 g / 10 min, 30 g / 10 min, 35 g / 10 min, 40 g / 10 min under the conditions of a test temperature of 315° C. and a load of 10 kg according to ISO 1133-2022.

[0020] Optionally, the graft copolymer has a melt mass flow rate in the range of one or any two of 1.8 g / 10 min, 1.5 g / 10 min, 1.3 g / 10 min, 1.2 g / 10 min, 1.0 g / 10 min, 0.8 g / 10 min, 0.5 g / 10 min under the conditions of a test temperature of 190° C. and a load of 2.16 kg according to ISO 1133-2022.

[0021] Preferably, the PPS / PPE composite material further comprises 0.1-3.5 parts of a processing aid, wherein the processing aid is at least one of a lubricant, a colorant and an antioxidant.

[0022] Optionally, the weight portion of the antioxidant is 0.1-0.5 parts, and the antioxidant is at least one of a hindered phenol antioxidant and a phosphite antioxidant, such as antioxidant 168 (tris[2.4-di-tert-butylphenyl]phosphite), antioxidant 1010 (pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate), etc.

[0023] Optionally, the weight portion of the lubricant is 0.1-1 part, and the lubricant is at least one of stearates, stearic acid esters, and ethylene bis stearic acid amides, such as pentaerythritol stearate, zinc stearate, and the like.

[0024] Optionally, the weight portion of the colorant is 0.1-2 parts, and the colorant is at least one of zinc sulfide, carbon black, iron red, titanium dioxide, and iron yellow.

[0025] In addition, the present invention provides a method for preparing the PPS / PPE composite material, comprising the following steps: mixing the components in proportion, melt-extruding, and granulating to obtain the PPS / PPE composite material.

[0026] Furthermore, the present invention provides application of the PPS / PPE composite material in the automotive field.

[0027] Specifically, the present invention provides the use of the PPS / PPE composite material in the preparation of an automobile extrusion cooling pipeline or an extrusion liquid cooling plate.

[0028] Compared with the prior art, the beneficial effects of the present invention are as follows: the present invention selects graft copolymers with specific main chains and side chains, which can take into account both PPS and PPE components, can effectively improve the compatibility of PPS / PPE, and can also improve the elongation at break of the material while maintaining heat resistance. At the same time, the use of the graft copolymers with specific main chains and side chains of the present invention can produce very little carbide during decomposition during processing, and the quality of the PPS / PPE alloy is better. DETAILED DESCRIPTION

[0029] In order to better illustrate the purpose, technical scheme and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments. Its purpose is to understand the content of the present invention in detail, rather than to limit the present invention. All other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise specified, the experimental reagents and instruments designed for the implementation and comparative examples of the present invention are all commonly used ordinary reagents and instruments, which can be obtained from commercial channels. In the implementation and comparative examples, the experimental methods used are conventional methods unless otherwise specified; and unless otherwise specified, the raw materials used in parallel experiments are the same batch of raw materials.

[0030] The raw materials used in the embodiments and comparative examples are described below, but are not limited to these materials:

[0031] PPS-1: melt mass flow rate 180g / 10min (316℃ / 5kg), manufacturer Xinhecheng, brand PPS-3418, pH value 5.5;

[0032] PPS-2: melt mass flow rate 150g / 10min (316℃ / 5kg), manufacturer Binhua, brand PPS-Q210, pH value 6.8;

[0033] PPS-3: melt mass flow rate 80g / 10min (316℃ / 5kg), manufacturer Xinhecheng, brand PPS 3508, pH value 7.8;

[0034] PPS-4: melt mass flow rate 350g / 10min (316℃ / 5kg), manufacturer Tongling, brand PPS 2035, pH value 8.8

[0035] PPS-5: melt mass flow rate 180g / 10min (316℃ / 5kg), manufacturer Xinhecheng, brand PPS3418HA, pH value 4.3;

[0036] PPE-1: melt mass flow rate 35g / 10min (315℃ / 10kg), Bluestar, brand PPE LXN040;

[0037] PPE-2: melt mass flow rate 15g / 10min (315℃ / 10kg), Zhongmu, brand PPE ZM045;

[0038] Graft copolymer-1: main chain PE, side chain PS, manufacturer: NOF Corporation, A1100;

[0039] Graft copolymer-2: main chain PE, side chain AS, manufacturer: NOF Corporation, A1401;

[0040] Graft copolymer-3: main chain EBA, side chain PS, manufacturer GRAFT POLYMER, GRAFTALLOY EB-PS;

[0041] Graft copolymer-4: main chain PP, side chain AS, NOF Corporation, A3400;

[0042] Graft copolymer-5: main chain EGMA, side chain PS, NOF Corporation, A4100;

[0043] Graft copolymer-6: main chain EEA, side chain AS, NOF Corporation, A5400;

[0044] Graft copolymer-7: main chain PC, side chain PS, NOF Corporation, CL130D;

[0045] Styrene-GMA copolymer: Styrene-GMA copolymer, manufacturer Jiayirong, brand SG-06;

[0046] SEBS-g-MAH: manufacturer Kraton, brand SEBS FG1901 G;

[0047] The antioxidant is a composite of a commercially available hindered phenol antioxidant 1010 and a commercially available phosphite antioxidant 168 in a mass ratio of 1:1.

[0048] The lubricant is pentaerythritol stearate, which is commercially available.

[0049] Examples 1-12 and Comparative Examples 1-7

[0050] The PPS / PPE composite material of the present invention has the following components as shown in Table 1 and Table 2. The preparation method of the PPS / PPE composite material comprises the following steps:

[0051] The components are mixed in proportion, melt-extruded through a twin-screw extruder, and granulated to obtain the PPS / PPE composite material; the temperature of each section of the twin-screw extruder is 220-320°C.

[0052] Performance Testing

[0053] Test standard:

[0054] Heat deformation temperature: Test standard ISO 75-2-2013, test condition 1.8MPa.

[0055] Elongation at break: Test standard ISO 527-2-2012, test conditions 50 mm / min, 23°C.

[0056] Evaluation of carbonization points during extrusion molding: The PPS / PPE composite materials prepared in the examples of the present invention and the comparative examples were injected into a Haake rheometer and extruded into PPS hollow tubes. After continuous extrusion for 1 minute, 1 m of the tubes were collected and the number of carbonization points on the surface of the tubes was observed.

[0057] The test results are shown in Table 1-2.

[0058] Table 1

[0059]

[0060]

[0061] Table 2

[0062]

[0063] It can be seen from the above table that the PPS / PPE composite material prepared in the embodiment of the present invention has a heat deformation temperature of >105°C, an elongation at break of >30%, and the number of carbonization points of ≤2.

[0064] From the comparison of Example 1, Examples 6-9, and Comparative Examples 1-4, it can be seen that the present invention selects a graft copolymer with a specific main chain and side chain, which can take into account both PPS and PPE components, can effectively improve the compatibility of PPS / PPE, and can also improve the elongation at break of the material while maintaining heat resistance. At the same time, the use of the graft copolymer with a specific main chain and side chain of the present invention produces very little carbide during decomposition during processing, and the quality of the PPS / PPE alloy is better. When the main chain is one of an ethylene copolymer and a propylene copolymer, the elongation at break is higher and the heat resistance is better.

[0065] Comparative Example 1 uses graft copolymer-7 with PC as the main chain and PS as the side chain. When the main chain of the graft copolymer is polycarbonate (PC), it cannot effectively entangle with the chain segments of PPS and PPE, which deteriorates the elongation. Comparative Example 2 uses styrene-GMA copolymer, which has too strong entanglement with the chain segments of PPS and PPE, which also deteriorates the elongation. Comparative Example 3 uses SEBS-g-MAH, which leads to a significant decline in heat resistance. At the same time, the elastomer itself is not heat resistant enough, which leads to carbonization points during production.

[0066] From the comparison between Example 1, Examples 10-12 and Comparative Example 5, it can be seen that when the PPS / PPE composite material includes the following components in parts by weight: 70-80 parts of polyphenylene sulfide resin, 10-15 parts of polyphenylene ether resin, and 5-8 parts of graft copolymer, the heat deformation temperature is higher, the elongation at break is greater, and the number of carbonization points is less.

[0067] From the comparison between Examples 1-3 and Comparative Examples 6-7, it can be seen that when the pH value of the polyphenylene sulfide resin is 5-8, the heat deformation temperature is higher, the elongation at break is greater, and the number of carbonization points is less.

[0068] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A PPS / PPE composite material, characterized in that: The invention comprises the following components in parts by weight: 50-90 parts of polyphenylene sulfide resin, 5-20 parts of polyphenylene ether resin, and 3-10 parts of graft copolymer; The graft copolymer comprises a main chain and a side chain, the main chain is one of polyethylene, polypropylene, ethylene copolymer and propylene copolymer, and the side chain is one of polystyrene and styrene copolymer; the pH value of the polyphenylene sulfide resin is 5-8.

2. The PPS / PPE composite material according to claim 1, characterized in that: The main chain of the graft copolymer is one of an ethylene copolymer and a propylene copolymer.

3. The PPS / PPE composite material according to claim 1 or 2, characterized in that: The ethylene copolymer includes one of ethylene-glycidyl methacrylate, ethylene-ethyl acrylate copolymer, and ethylene-butyl acrylate copolymer; the propylene copolymer includes one of propylene-glycidyl methacrylate and propylene-ethyl acrylate copolymer.

4. The PPS / PPE composite material according to claim 1, characterized in that: The styrene copolymer includes one of a styrene-acrylonitrile copolymer and a styrene-acrylonitrile-glycidyl methacrylate copolymer.

5. The PPS / PPE composite material according to claim 1, characterized in that: The invention comprises the following components in parts by weight: 70-80 parts of polyphenylene sulfide resin, 10-15 parts of polyphenylene ether resin and 5-8 parts of graft copolymer.

6. The PPS / PPE composite material according to claim 1, characterized in that: The polyphenylene sulfide resin has a melt mass flow rate of ≤300 g / 10 min at a test temperature of 316° C. and a load of 5 kg according to ISO 1133-2022; the polyphenylene ether resin has a melt mass flow rate of 10-40 g / 10 min at a test temperature of 315° C. and a load of 10 kg according to ISO 1133-2022; and the graft copolymer has a melt mass flow rate of <2 g / 10 min at a test temperature of 190° C. and a load of 2.16 kg according to ISO 1133-2022.

7. The PPS / PPE composite material according to claim 1, characterized in that: The PPS / PPE composite material further includes 0.1-3.5 parts of a processing aid, wherein the processing aid is at least one of a lubricant, a colorant, and an antioxidant.

8. A method for preparing a PPS / PPE composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The components are mixed in proportion, melt-extruded and granulated to obtain the PPS / PPE composite material.

9. Use of the PPS / PPE composite material according to any one of claims 1 to 7 in the automotive field.

10. Use of the PPS / PPE composite material according to any one of claims 1 to 7 in the preparation of automobile extrusion cooling pipelines or extrusion liquid cooling plates.

Citation Information

Patent Citations

  • Polyphenylene sulfide resin composition

    CN101084273A

  • Polyphenylene sulfide resin composition as well as preparation method and application thereof

    CN112708276A

  • Extruded and rolled polyphenylene sulfide copper-clad plate material and preparation method thereof

    CN114106558A

  • Polyphenylene ether-containing resin composition and method of producing the same

    JP2012224754A

  • Polyphenylene Sulfide Compositions for Laser Direct Structuring Processes and the Shaped Articles Therefore

    US20240076494A1